Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 188591 by 073 last updated on 03/Mar/23

Commented by manxsol last updated on 03/Mar/23

x=−2  f(−2)=f(−2)−5(−2)+3m  ((−10)/3)=m    ???

$${x}=−\mathrm{2} \\ $$$${f}\left(−\mathrm{2}\right)={f}\left(−\mathrm{2}\right)−\mathrm{5}\left(−\mathrm{2}\right)+\mathrm{3}{m} \\ $$$$\frac{−\mathrm{10}}{\mathrm{3}}={m}\:\:\:\:??? \\ $$

Commented by 073 last updated on 03/Mar/23

no

$$\mathrm{no} \\ $$

Commented by Frix last updated on 04/Mar/23

Yes!

$$\mathrm{Yes}! \\ $$

Answered by floor(10²Eta[1]) last updated on 03/Mar/23

f(2x+2)=f(x)−5x+3m  2f′(2x+2)=f′(x)−5  x=−2⇒2(2m+1)=2m+1−5  ⇒4m+2=2m−4⇒2m=−6⇒m=−3

$$\mathrm{f}\left(\mathrm{2x}+\mathrm{2}\right)=\mathrm{f}\left(\mathrm{x}\right)−\mathrm{5x}+\mathrm{3m} \\ $$$$\mathrm{2f}'\left(\mathrm{2x}+\mathrm{2}\right)=\mathrm{f}'\left(\mathrm{x}\right)−\mathrm{5} \\ $$$$\mathrm{x}=−\mathrm{2}\Rightarrow\mathrm{2}\left(\mathrm{2m}+\mathrm{1}\right)=\mathrm{2m}+\mathrm{1}−\mathrm{5} \\ $$$$\Rightarrow\mathrm{4m}+\mathrm{2}=\mathrm{2m}−\mathrm{4}\Rightarrow\mathrm{2m}=−\mathrm{6}\Rightarrow\mathrm{m}=−\mathrm{3} \\ $$

Commented by 073 last updated on 03/Mar/23

nice solution

$$\mathrm{nice}\:\mathrm{solution} \\ $$

Answered by qaz last updated on 03/Mar/23

f(2x+2)=f(−2)+f(−2)′(2x+4)+...    ,  f(x)=f(−2)+f(−2)′(x+2)+...  ⇒(2m+1)(2x+4)+...=(2m+1)(x+2)−5x+3m+...  ⇒(2m+1)∙2x=(2m+1)x−5x  ⇒m=−3

$${f}\left(\mathrm{2}{x}+\mathrm{2}\right)={f}\left(−\mathrm{2}\right)+{f}\left(−\mathrm{2}\right)'\left(\mathrm{2}{x}+\mathrm{4}\right)+...\:\:\:\:, \\ $$$${f}\left({x}\right)={f}\left(−\mathrm{2}\right)+{f}\left(−\mathrm{2}\right)'\left({x}+\mathrm{2}\right)+... \\ $$$$\Rightarrow\left(\mathrm{2}{m}+\mathrm{1}\right)\left(\mathrm{2}{x}+\mathrm{4}\right)+...=\left(\mathrm{2}{m}+\mathrm{1}\right)\left({x}+\mathrm{2}\right)−\mathrm{5}{x}+\mathrm{3}{m}+... \\ $$$$\Rightarrow\left(\mathrm{2}{m}+\mathrm{1}\right)\centerdot\mathrm{2}{x}=\left(\mathrm{2}{m}+\mathrm{1}\right){x}−\mathrm{5}{x} \\ $$$$\Rightarrow{m}=−\mathrm{3} \\ $$

Commented by 073 last updated on 03/Mar/23

nice solution

$$\mathrm{nice}\:\mathrm{solution} \\ $$

Answered by CElcedricjunior last updated on 03/Mar/23

f(2x+2)=f(x)−5x+3m  f′(−2)=2m+1   (1)  calculons m  f(2x+2)=f(x)−5x+3m ■Cedric junior  =>2f′(2x+2)=f′(x)−5  =>f′(−2)=−5 (2)  (1)=(2)=>−5=2m+1=>m=−3 ★Moivre   determinant (((m=−3)),((f′(−2)=−5)))

$$\boldsymbol{{f}}\left(\mathrm{2}\boldsymbol{{x}}+\mathrm{2}\right)=\boldsymbol{{f}}\left(\boldsymbol{{x}}\right)−\mathrm{5}\boldsymbol{{x}}+\mathrm{3}\boldsymbol{{m}} \\ $$$$\boldsymbol{{f}}'\left(−\mathrm{2}\right)=\mathrm{2}\boldsymbol{{m}}+\mathrm{1}\:\:\:\left(\mathrm{1}\right) \\ $$$$\boldsymbol{{calculons}}\:\boldsymbol{{m}} \\ $$$$\boldsymbol{{f}}\left(\mathrm{2}\boldsymbol{{x}}+\mathrm{2}\right)=\boldsymbol{{f}}\left(\boldsymbol{{x}}\right)−\mathrm{5}\boldsymbol{{x}}+\mathrm{3}\boldsymbol{{m}}\:\blacksquare\mathscr{C}{edric}\:{junior} \\ $$$$=>\mathrm{2}\boldsymbol{{f}}'\left(\mathrm{2}\boldsymbol{{x}}+\mathrm{2}\right)=\boldsymbol{{f}}'\left(\boldsymbol{{x}}\right)−\mathrm{5} \\ $$$$=>\boldsymbol{{f}}'\left(−\mathrm{2}\right)=−\mathrm{5}\:\left(\mathrm{2}\right) \\ $$$$\left(\mathrm{1}\right)=\left(\mathrm{2}\right)=>−\mathrm{5}=\mathrm{2}\boldsymbol{{m}}+\mathrm{1}=>\boldsymbol{{m}}=−\mathrm{3}\:\bigstar{Moivre} \\ $$$$\begin{array}{|c|c|}{\boldsymbol{{m}}=−\mathrm{3}}\\{\boldsymbol{{f}}'\left(−\mathrm{2}\right)=−\mathrm{5}}\\\hline\end{array} \\ $$$$ \\ $$

Commented by 073 last updated on 03/Mar/23

nice solution

$$\mathrm{nice}\:\mathrm{solution} \\ $$

Answered by Frix last updated on 04/Mar/23

The first equation alone gives  m=−((10)/3)  because it must be true for x=−2:  f(2×(−2)+2)=f(−2)−5×(−2)+3m  f(−2)=f(−2)+10+3m  0=10+3m  m=−((10)/3)    We don′t know f(x) ⇒ f′(−2) can have  any value, why not 2m+1=−((17)/3)?

$$\mathrm{The}\:\mathrm{first}\:\mathrm{equation}\:\mathrm{alone}\:\mathrm{gives} \\ $$$${m}=−\frac{\mathrm{10}}{\mathrm{3}} \\ $$$$\mathrm{because}\:\mathrm{it}\:\mathrm{must}\:\mathrm{be}\:\mathrm{true}\:\mathrm{for}\:{x}=−\mathrm{2}: \\ $$$${f}\left(\mathrm{2}×\left(−\mathrm{2}\right)+\mathrm{2}\right)={f}\left(−\mathrm{2}\right)−\mathrm{5}×\left(−\mathrm{2}\right)+\mathrm{3}{m} \\ $$$${f}\left(−\mathrm{2}\right)={f}\left(−\mathrm{2}\right)+\mathrm{10}+\mathrm{3}{m} \\ $$$$\mathrm{0}=\mathrm{10}+\mathrm{3}{m} \\ $$$${m}=−\frac{\mathrm{10}}{\mathrm{3}} \\ $$$$ \\ $$$$\mathrm{We}\:\mathrm{don}'\mathrm{t}\:\mathrm{know}\:{f}\left({x}\right)\:\Rightarrow\:{f}'\left(−\mathrm{2}\right)\:\mathrm{can}\:\mathrm{have} \\ $$$$\mathrm{any}\:\mathrm{value},\:\mathrm{why}\:\mathrm{not}\:\mathrm{2}{m}+\mathrm{1}=−\frac{\mathrm{17}}{\mathrm{3}}? \\ $$

Commented by manxsol last updated on 05/Mar/23

Thanks,Sir Frix

$${Thanks},{Sir}\:{Frix} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com